2015
DOI: 10.1186/s12931-015-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-myofibroblast transition is differentially regulated by bronchial epithelial cells from asthmatic children

Abstract: BackgroundAirway remodeling is a proposed mechanism that underlies the persistent loss of lung function associated with childhood asthma. Previous studies have demonstrated that human lung fibroblasts (HLFs) co-cultured with primary human bronchial epithelial cells (BECs) from asthmatic children exhibit greater expression of extracellular matrix (ECM) components compared to co-culture with BECs derived from healthy children. Myofibroblasts represent a population of differentiated fibroblasts that have greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…In vivo animal models of airway remodeling [147149] and descriptive data from human bronchial biopsies [150152] suggest the airway epithelium secretes proteins that regulate lung fibroblasts and airway remodeling with increased ECM deposition, including TGF-β [150, 153–155], VEGF [151, 156159], periostin [160, 161], activin A [162164], and follistatins [165, 166]. Furthermore, recent ex vivo investigations using primary bronchial epithelial cells (BECs) from asthmatic and healthy children demonstrated that when co-cultured with BECs from healthy children, lung fibroblast expression of types I and III collagen, hyaluronan, as well as expression of α-SMA, indicative of a myofibroblast phenotype, are downregulated [167, 168]. This downregulation is diminished in fibroblasts co-cultured with asthmatic BECs [167, 168], suggesting that, in addition to stimulatory signals, there must be epithelial-derived factors that inhibit fibroblasts and FMT, such that in normal airways, a balance of epithelial-secreted stimulatory and inhibitory factors that regulate fibroblasts and ECM deposition.…”
Section: Chronic Changes To Airway Ecm In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo animal models of airway remodeling [147149] and descriptive data from human bronchial biopsies [150152] suggest the airway epithelium secretes proteins that regulate lung fibroblasts and airway remodeling with increased ECM deposition, including TGF-β [150, 153–155], VEGF [151, 156159], periostin [160, 161], activin A [162164], and follistatins [165, 166]. Furthermore, recent ex vivo investigations using primary bronchial epithelial cells (BECs) from asthmatic and healthy children demonstrated that when co-cultured with BECs from healthy children, lung fibroblast expression of types I and III collagen, hyaluronan, as well as expression of α-SMA, indicative of a myofibroblast phenotype, are downregulated [167, 168]. This downregulation is diminished in fibroblasts co-cultured with asthmatic BECs [167, 168], suggesting that, in addition to stimulatory signals, there must be epithelial-derived factors that inhibit fibroblasts and FMT, such that in normal airways, a balance of epithelial-secreted stimulatory and inhibitory factors that regulate fibroblasts and ECM deposition.…”
Section: Chronic Changes To Airway Ecm In Asthmamentioning
confidence: 99%
“…Furthermore, recent ex vivo investigations using primary bronchial epithelial cells (BECs) from asthmatic and healthy children demonstrated that when co-cultured with BECs from healthy children, lung fibroblast expression of types I and III collagen, hyaluronan, as well as expression of α-SMA, indicative of a myofibroblast phenotype, are downregulated [167, 168]. This downregulation is diminished in fibroblasts co-cultured with asthmatic BECs [167, 168], suggesting that, in addition to stimulatory signals, there must be epithelial-derived factors that inhibit fibroblasts and FMT, such that in normal airways, a balance of epithelial-secreted stimulatory and inhibitory factors that regulate fibroblasts and ECM deposition. Other studies have shown that airway epithelial cells synthesize hyaluronan and its degradative enzymes, the hyaluronidases (Hyals), in response to oxidative stress and other injurious agents [169174] and that hyaluronan-enriched ECM synthesized by respiratory epithelial cells can impact monocyte adhesion [175].…”
Section: Chronic Changes To Airway Ecm In Asthmamentioning
confidence: 99%
“…It begins with a dedifferentiation period, then using an air-liquid interface culture allows a 21-28 day period for production of fully differentiated pseudostratified bronchial epithelium similar to the epithelium observed on the initial endobronchial biopsies (figure 2) [10]. These culture systems can also mimic cellular crosstalk through the air-blood barrier when co-culturing bronchial epithelial cells with inflammatory cells such as mast cells [20], fibroblasts [21] and macrophages [22]. The culture of bronchial epithelial cells allows the differentiation process in health and disease to be understood.…”
Section: Culture Of Bronchial Epithelial Cellsmentioning
confidence: 99%
“…Transformed deposition and composition of extracellular matrix proteins and hyperplasia of mucous gland is also noted. 15 One noteworthy characteristic of the epithelium is its ability to defend itself against oxidant injury, which is a characteristic enabling us to partially explain why asthmatic patients are hypersensitive to oxidant pollutants such as tobacco smoke. 16…”
Section: Airway Epitheliummentioning
confidence: 99%